Oil Price Volatility and Unemployment in Iraq: A Two-Stage Approach Using Generalized Autoregressive Conditional Heteroskedasticity-Mixed-Data Sampling - Abed, Zainab Ahmed; Barguellil, Achouak; Fathalla, Mohamed Mahmoud (International Journal of Energy Economics and Policy, 2025)
Iraq is a rentier economy heavily reliant on oil revenues as the primary source of public spending and development financing. Under this dependency, oil price volatility plays a critical role in shaping macroeconomic performance, particularly in the labor market. This study investigates the relationship between oil price volatility and unemployment in Iraq during the period 1991-2023. A two-stage approach was adopted: Oil price volatility was first estimated using the GARCH model, followed by an assessment of its dynamic impact on unemployment through the MIDAS technique. The findings reveal a significant positive relationship, indicating the vulnerability of Iraq’s labor market to external energy shocks. The lag structure indicates a nonlinear effect - strong initially, then gradually fading, before slightly reemerging - aligning with the hypothesis of economic sluggishness. Additionally, the study identifies structural imbalances in the Iraqi economy, as traditional relationships such as Okun’s Law and the Phillips Curve do not hold. This suggests that labor market dynamics in Iraq diverge from conventional economic models, shaped instead by the characteristics of a rentier system and its institutional and political constraints. The results underscore the importance of diversifying income sources and investing in human capital to enhance labor market resilience and reduce dependency on oil revenues.